PARADIGM OF ASSOCIATIVE THINKING THROUGH A SCIENTIFIC APPROACH IN THE 2013 CURRICULUM CONCEPT - Nurzannah Nurzannah (Proceeding International Seminar of Islamic Studies, 2021)
The concept of the scientific learning approach in the 2013 curriculum contains 5 principles, namely observing, asking, reasoning, associating, and communicating-creating. This study specifically wants to discuss the fourth principle, namely: association. Association in principle is to think associative. Associative thinking that is carried out by students is the key to the scientific approach. The scientific approach developed by the teacher in the classroom is not just a process of observing, questioning, reasoning, associating, and communicating, but it is more than the expectations we imagine. Associative thinking will spur activities to observe, ask questions (both to oneself and others), the reason more logically, and critically, and must communicate it to the teacher (experts), and can build creativity. This associative thinking activity will repeat itself to the point of saturation, which finding knowledge or a way out of a problem, both from questions raised by teachers and from fellow students, even from students themselves.Keywords: Scientific Approach, Associative Thinking, And The 2013 Curriculum.